VDR Gene Polymorphisms in Kurdish Population and Its Relation to T1DM in Erbil-Iraq - Othman, Galawezh Obaid (Cellular and Molecular Biology, 2022)
This research assessed the relationship among type 1 diabetes VDR gene polymorphisms (ApaI and TaqI) in the Kurdish population in Erbil-Iraq. Forty individuals with type 1 diabetes and thirty healthy people were recruited from the Kurdish population in Erbil, Iraq. Genomic DNA was taken from blood, being genotyped for SNP (single nucleotide polymorphisms). The distribution of VDR polymorphisms in two restriction fragment length polymorphism sites, TaqI and ApaI, was investigated in patients and controlled by a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) utilizing ApaI and TaqI restriction enzymes. Using SPSS software (V15.0), the genotype dispersal and allelic incidences in patients and controls were compared. VDR polymorphism genotype dispersal and allele incidences vary dramatically among patients and controls. The results confirmed that the genotype GT in SNP ApaI was a risk factor among type 1 diabetes mellitus patients’ combination that imparted the strongest susceptibility to T1DM (P=0.00023). Still, the SNP TaqI showed no relevance between cases and controls (P=0.35). Our findings indicate that VDR gene polymorphisms in the combination of genotypes are related to an increased risk of T1DM in the Kurdish community and warrant further investigation as a possible genetic risk marker for T1DM. More research is needed to corroborate this finding, particularly the VDR gene, which was studied for the first time in the Kurdish population.